Determinants of the Successful Digital Campaigns on Zakat: an Analysis Based on Islamic Marketing Perspective - Juliana Nasution (Universitas Muhammadiyah Ponorogo, 2023)
Zakat campaigns have taken place from time to time in various phases of muslim history. The zakat campaign has been said to be effective, but evidence in Indonesia shows that the zakat literacy of muslim communities is not yet high, they also tend to choose to distribute zakat directly, and there is a wide gap between the potential and reality of zakat collection. This study aims to examine the determinants that influence the success of a digital zakat campaign, consisting of content or messages in the zakat campaign, amil or zakat campaigners, campaign target digital literacy, social media as a campaign platform, and campaign methods. This research is a quantitative research, with respondents consisting of 100 muzakki (zakat donator) at LAZ Dompet Dhuafa Waspada North Sumatra, Indonesia. Data analysis techniques using descriptive statistics and SEM-PLS using SmartPLS 4.0 software. The results of the study show that content and social media have an effect but not significant on the success of the zakat digital campaign. Meanwhile, the amil factor and campaign method have a significant effect on the success of the zakat digital campaign. Meanwhile, digital literacy has a negative and insignificant effect on digital zakat campaigns. The results of this study indicate the importance of amil positioning in the success of the zakat campaign. This study proposes that zakat institutions cadre their own amil celebrities.